Simple Thermal Analysis as a Green Method for the Detection of Meat Adulteration - Ilma Nugrahani; Aditya Aditya (Universitas Gadjah Mada, 2023)
Differential scanning calorimetry (DSC) is one of the most widely developed thermal analysis methods for meat samples for halal authentication of food or processed products. Research on adulteration detection for various types of meat and its derivatives has been developed before and still requires organic solvents. Therefore, the concept of the